Thermal and kinetic studies of white lupin (Lupinus albus) oil - Fontanari, Gustavo Guadagnucci; Kobelnik, Marcelo; Marques, Marcelo Rodrigues; Arêas, José Alfredo Gomes; Franzin, Bruno Trevizan [UNESP]; Pastre, Iêda Aparecida [UNESP]; Fertonani, Fernando Luis [UNESP] (Springer Nature, 2018)
The aim of this work was to evaluate the thermal and kinetic behavior of white lupin (Lupinus albus) oil obtained from its seeds. White lupin is a seed from the Lupinus albus species, and it presents physicochemical and physiological functional properties and is rich in fiber, protein, and lipids with a great application potential. Oil was extracted from the seeds, and its fatty acid profile indicates predominantly monounsaturated fatty acids (~65%). Thermo-gravimetry, derivative thermo-gravimetry, and differential scanning calorimetry (DSC) were used to characterize the thermal behavior of the oil fraction at high temperatures, showing a good thermal stability between 222 and 230 °C and a large heat delivery at T = 400 °C. Additionally, DSC was performed from 25 to −60 °C, in which the crystallization behavior was verified. The kinetic behavior of the thermal decomposition was evaluated from several β values and mass samples (5 and 20 mg) under nitrogen and oxygen atmospheres to comparisons of the data.
Keywords: Fatty acids composition; Lupin oil; Thermal behavior; Transition phase